2006
DOI: 10.1243/095441105x69079
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned from early clinical experience and results of 300 ASR® hip resurfacing implantations

Abstract: Between August 2003 and April 2005, 300 ASR metal-on-metal resurfacing hip endoprostheses were implanted by the first author and a fellow surgeon. The mean age at surgery was 56.8 years (18-75.9 years) and mean body mass index was 27.6 kg/m2 (range, 19-41 kg/m2). The mean follow-up time was 202 days. The mean Harris hip score improved from 44 pre-operatively to 89 at 3 months post-operatively. In total, eight (2.7 per cent) cases [five neck fractures (1.66 per cent) and three cup revisions (1 per cent)] were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 25 publications
3
45
0
Order By: Relevance
“…[50][51][52][53][54][55][56][57][58][59] However, complications particular to this procedure have been identified (as stated previously), and emphasis is placed on patient selection, component selection and surgical technique to avoid poor and adverse outcomes and short-term failures. 44,47,[60][61][62][63][64][65][66][67][68][69][70] Many surgeons avoid resurfacing in postmenopausal women because of an increased risk of femoral neck fracture, and in those with known renal insufficiency owing to the potential for metal ion accumulation.…”
Section: Obesitymentioning
confidence: 99%
“…[50][51][52][53][54][55][56][57][58][59] However, complications particular to this procedure have been identified (as stated previously), and emphasis is placed on patient selection, component selection and surgical technique to avoid poor and adverse outcomes and short-term failures. 44,47,[60][61][62][63][64][65][66][67][68][69][70] Many surgeons avoid resurfacing in postmenopausal women because of an increased risk of femoral neck fracture, and in those with known renal insufficiency owing to the potential for metal ion accumulation.…”
Section: Obesitymentioning
confidence: 99%
“…Several case series indicate that improvement in technique and increased experience resulted in a decrease in revision rates and better functional outcome scores (Siebel et al, 2006;Mont et al, 2007;Amstutz et al, 2007;Amstutz et al, 2011). However, this was not found in another large series (McBryde et al, 2010).…”
Section: Surgery Related Parametersmentioning
confidence: 99%
“…More recently, MoM related issues such as pseudotumors (Figs. 2 and 3), high blood ion levels and allergy towards Co-Cr ions have raised additional concerns against the use of HRA (Davies et al, 2005;Willert et al, 2005;Siebel et al, 2006;De Haan et al, 2008). Ollivere et al (2009) reported a 1.9% incidence of metallosis as the indication for the early failure in a consecutive series of 493 Birmingham HRA.…”
Section: Failure Of Hramentioning
confidence: 99%
See 2 more Smart Citations